2014
DOI: 10.1007/s11605-013-2339-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Incidental Pulmonary Nodules in Esophageal Cancer Patients

Abstract: Incidental pulmonary nodules in the absence of extra-pulmonary metastases in esophageal cancer patients are rarely metastases and should not bias caregivers towards palliative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Although the clinical significance and natural history of SRIF are still undetermined, it is highly prevalent, and characterization as SRIF in diagnostic reports is preferable to non-specific descriptions of subpleural fibrosis to prevent misinterpretation as potential UIP, which is characterized by a different histologic pattern of subpleural fibrosis and has a poor prognosis. Consistent with other histopathology studies [2,3,25], interstitial and peribronchial non-necrotizing granulomas were common, identified in 8% of patients in this series. This HP-like pattern has been previously described as a secondary cell-mediated response adjacent to malignant tumors or in regional lymph nodes [26]; however, we also observed granulomas in patients with benign diagnoses, suggesting that the pattern is likely not wholly attributable to antitumor response.…”
Section: Discussionsupporting
confidence: 92%
“…Although the clinical significance and natural history of SRIF are still undetermined, it is highly prevalent, and characterization as SRIF in diagnostic reports is preferable to non-specific descriptions of subpleural fibrosis to prevent misinterpretation as potential UIP, which is characterized by a different histologic pattern of subpleural fibrosis and has a poor prognosis. Consistent with other histopathology studies [2,3,25], interstitial and peribronchial non-necrotizing granulomas were common, identified in 8% of patients in this series. This HP-like pattern has been previously described as a secondary cell-mediated response adjacent to malignant tumors or in regional lymph nodes [26]; however, we also observed granulomas in patients with benign diagnoses, suggesting that the pattern is likely not wholly attributable to antitumor response.…”
Section: Discussionsupporting
confidence: 92%
“…Pulmonary nodules are incidental lesions that are frequently identified on imaging for other clinical indications. The subsequent management and follow-up of these lesions is variable and largely dependent on the nodule size, imaging modality and associated clinical features [ 17 – 19 ]. Wu et al [ 20 ] suggest that small pulmonary nodules in patients less than 50 years old with no history of malignancy are unlikely to be of clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…This report also strongly supports our results, but there are many differences from our study in terms of the historical context, treatment, and the size of nodules. In the third report, 30 patients with lung nodules showed no increase in the size of the nodules on follow-up CT at 9 months (range, 3-40) after esophagectomy [25]. However, our study differed in that our patients had squamous cell carcinoma, a larger number of nodules were evaluated, and our follow-up period was longer.…”
Section: Discussionmentioning
confidence: 63%
“…According to those guidelines, if a patient has a pulmonary solid nodule <10 mm as a maximal diameter, nodule progression should be monitored whether or not the patient is a smoker. Three previous studies reported on the outcome of pulmonary nodules in esophageal cancer patients who had both resectable cancer and minute pulmonary nodules after subtotal esophagectomy [23][24][25]. In the first report, only 3 esophageal cancer patients (9%) proved to develop metastatic pulmonary disease in the follow-up who had pulmonary nodules found in their preoperative stage, and received NAC followed by surgery [23].…”
Section: Discussionmentioning
confidence: 99%